Addressing the Environment Electrostatic Effect on Ballistic Electron Transport in Large Systems: A QM/MM-NEGF Approach - Feliciano, Gustavo T. [UNESP]; Sanz-Navarro, Carlos; Coutinho-Neto, Mauricio Domingues; Ordejón, Pablo; Scheicher, Ralph H.; Rocha, Alexandre Reily [UNESP] (American Chemical Society (ACS), 2018)
The effects of the environment in nanoscopic materials can play a crucial role in device design. Particularly in biosensors, where the system is usually embedded in a solution, water and ions have to be taken into consideration in atomistic simulations of electronic transport for a realistic description of the system. In this work, we present a methodology that combines quantum mechanics/molecular mechanics methods (QM/MM) with the nonequilibrium Green's function framework to simulate the electronic transport properties of nanoscopic devices in the presence of solvents. As a case in point, we present further results for DNA translocation through a graphene nanopore. In particular, we take a closer look into general assumptions in a previous work. For this sake, we consider larger QM regions that include the first two solvation shells and investigate the effects of adding extra k-points to the NEGF calculations. The transverse conductance is then calculated in a prototype sequencing device in order to highlight the effects of the solvent.